EXPLANATION STUDY OF AGRO-INDUSTRIAL FIRM FINANCIAL PERFORMANCE BASED ON CAPITAL STRUCTURE AND FIRM STRATEGY IN THE COVID-19 PANDEMIC - Agung Budi Sulistiyo; Bunga Maharani; Bayu Aprillianto; Novi Wulandari Widiyanti; Muhammad Miqdad (Universitas Airlangga, 2022)
The purpose of this study was to examine the effect of corporate strategy on financial performance with capitalstructure as an intervening variable. The advantage of this research lies in taking the object of the company inthe agroindustry sector in the Covid-19 pandemic situation which has not been the concern of researchers. Thepopulation is all agroindustry companies, listed in Indonesian Stock Exchange. Data collection technique usingpurposive sampling method and a total of 52 sample data were obtained with a time span of 2020-2021 whichwere processed using the multiple regression method. The results show that there is an effect of corporatestrategy on capital structure, as well as capital structure that affects financial performance. However, theopposite result is shown by the non-influence of corporate strategy variables on financial performance. Thus,the mediating role of capital structure in the relationship between corporate strategy and financial performancehas been clearly proven. The results of this study are able to provide future research recommendations in theform of using variations of company strategies that can have different implications, especially for companies inthe agroindustry sector during the covid-19 pandemic. In addition, this study also recommends companies tomanage their capital structure optimally to generate value to financial performance. This research will alsocontribute on the fast growth of literature related to corporate strategy, capital structure, and financialperformance as well as the development of agency theory, signal theory and pecking order theory.